PENGARUH LINGKUNGAN KERJA DAN KEPUASAN KERJA TERHADAP KINERJA PEGAWAI - Hantoro, Yanis Chrisna; Kurniawati, Desi Tri (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
The objective of this research is to identify and analyze the effects of workplace environment and job satisfaction on employee performance at the Cooperative, Micro Business, and Labor Agency of Kediri City. The population of this applied quantitative research is the employees of the Cooperative, Micro Business, and Labor Agency of Kediri City, from which forty people were selected as the respondents using probability sampling method. The results of the inferential statistical analysis and multiple linear regression have led to findings that workplace environment and job satisfaction significantly affect employee performance. The findings are an indication that the performance of employees at the Cooperative, Micro Business, and Labor Agency of Kediri City is determined by their workplace environment and job satisfaction.